Dampak Literasi Keuangan Terhadap Pengelolaan Utang Rumah Tangga - Dawolo, Asmiarni Putri; Sarumaha , Fanny Corsby Sella; Zebua, Jeli Susanti; Halawa, Herlinwati (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
Financial literacy plays an important role in helping individuals and families manage finances wisely, including in debt management. This study aims to analyze the impact of financial literacy on household debt management. Based on a literature review of various studies in the last five years, it is found that good financial literacy contributes to more effective financial decision-making, avoidance of excessive debt, and improved household welfare. Financial literacy not only influences the way households budget, but also provides a better understanding of the risks and benefits of using debt. As such, individuals with high levels of financial literacy tend to have better control over their finances and are able to manage debt more productively. The article draws on ten relevant academic journals to substantiate these findings and recommends the importance of ongoing financial education programs.